DESIGN OF WEBSITE-BASED SANTRI ATTENDANCE INFORMATION SYSTEM (CASE STUDY: RUMAH YATIM AND TAHFIDZ QUR'AN MADANI BANDUNG) - Mamok Andri Senubekti; Muhammad Yusron Fathul Islam (BEST, 2021)
In today's era of globalization, the advancement of information technology is accelerating. Computers connected to the internet or intranet created to facilitate human work are needed in all fields, especially in the field of education. Rumah Yatim and Tahfidz Qur'an Madani need a website-based attendance information system to help enter santri attendance data. For this reason, the author tried to create a journal about a web-based santri absence system that until now has not been computerized. Rumah Yatim and Tahfidz Qur'an Madani is one of the foundations in Bandung that until now the input of absenteeism is still manual ranging from the input of santri absentee data to the storage of absentee data that has been input and report making. So that it is possible when the process takes place data manipulation and data loss is very large. The design of this information system is the best solution to solve the problems in this foundation, and with a computerized system can be achieved an effective and efficient activity in supporting activities in this foundation.